English English - Aldila, Herman (Fakultas Teknik, Universitas Bangka Belitung, 2023)
Green technology through the implementation of hydroponic-based urban farming as an icon for the Surya Timur sub-district in the Kepulauan Bangka Belitung Province can become a brand awareness activity in order to promote and increase competitiveness so that it becomes a productive area after massive tin mining activities in the area. This activity began with coordination with the Village Head and Chair of the Surya Timur’s PKK in order to ensure readiness to implement the program as driving cadres. Apart from that, this activity involves hydroponic practitioners as assistants in managing hydroponic activities which include sowing, planting, caring for, and harvesting hydroponic commodities. It is hoped that optimizing the sub-district website can become an effective promotional medium in documenting these activities so that they can become a superior profile and be widely known by the public. This is expected to increase the opportunity to obtain competitive grants that can be used to improve the infrastructure of this area to become more productive and free from dependence on tin mining activities which have the potential to damage the area in the future.